AIR LEAK SYNDROME IN PATIENTS WITH SEVERE COVID PNEUMONIA - Naz, Arshi; Basma Salman,; Sidra Javed,; Samita S Khan,; Mohammad Tariq,; Mirza Shahzad Baig,; Vijai Kumar, (Journal of Ayub Medical College Abbottabad, 2022)
There are number of emerging studies that link the air leak syndrome (ALS) with COVID 19 disease but still data to explain the association, incidence and outcome in these patients is lacking. We aim to understand the risk factors and clinical outcome of these air leakage events in COVID 19 patients admitted to our institution. Methods. This is a single-centered case series conducted at the COVID unit of the SMBBIT in Karachi, Pakistan. Data collection was done from April 24, 2020 to June 10, 2021. Results: There were 19 patients with severe COVID pneumonia who developed air leaks. Most common finding was subcutaneous emphysema 94%. Four patients (21%) didn't receive positive pressure ventilation in any form. Median time of developing air leak from admission is 5 [2-9] and from PPV is 2 [1-3] days. There was high percentage of mortality 84.5 % in these patients.